POTENSI NONKARIOGENIK EKSTRAK DAUN Stevia rebaudianaBertoni SEBAGAI PEMANIS ALAMI PENGGANTI GULA - Sinta Deviyanti (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Dental caries is a disease that is produced by the dissolution of local chemical surfaces of the teeth caused by product of microbial fermentation from dietary carbohydrates in the biofilm that attached to the teeth. Sugar especially sucrose is the most important dietary factors in the etiology of dental caries. Dietary modification have been recommended in order to reduce the fermentable carbohydrate intake needed by the cariogenic microorganism in order to produce acid. The used of sugar substitutes is a common procedure to reduce caries risk. Stevia rebaudiana Bertoni leaves extract is a natural sweetener which is used as a sugar substitute. The aim of this literature review is to study the noncariogenic potencially of Stevia rebaudiana Bertoni leaves extracts as natural sweetener. Review: Stevia rebaudiana Bertoni leaves extract is a non caloric natural sweetener alternative source to traditional sugar (sucrose) with diterpene glycosides are responsible for its high sweetening taste ranging 250-400 times sweeter as compare to sucrose. Studies have revealed the noncariogenic potential of Stevia leaves extract because its non fermentable, improved the pH biofilm, pH saliva and buffering capacity of the saliva in a high caries risk patient and reduce cariogenic organisms in biofilm and saliva. Stevia rebaudiana Bertoni leaves extracts also have been scientifically proven to be safe and effective to protection against dental caries because of its less demineralization email as compared to sucrose. Conclusions: Stevia rebaudiana Bertoni leaves extracts as natural sweetener has a excellent noncariogenic potency